Greater adaptations with submaximal muscle lengthening than maximal shortening contractions - Hortobagyi, T.; Barrier, J.; Beard, D.; Braspennincx, J.; Koens, P.; de Vita, P.; Dempsey, L.; Israel, R.; Lambert, J. (Medicine & Science in Sports & Exercise, 1996)
It has been known for a long time that the strength demands of eccentric contractions far exceed those of concentric contractions in a coordinated movement. Studies which have used maximal eccentric load versus maximal concentric load have shown superior strength gains for eccentric training. This study controlled for load so that both forms of contraction were overloaded by the same amount. Ss were women. Eccentric contractions were still shown to develop significantly greater strength gains than concentric contractions despite the similarity of loads. Implication: Eccentric strength training, even under submaximal eccentric loads, produces better strength gains than concentric training. This suggests this might be a better form of rehabilitation strength training. However, the specificity of effects further support the contention that strength training is particularly specific and is likely to have little transfer to whole-body sporting activities.